The colonialists roots of the Mbanza Kongo world heritage project - Máximo, Bruno Pastre (Faculdade de Ciências e Letras - Unesp - Araraquara., 2018)
This article seeks to analyze the narrative by the Angolan government about the archaeological heritage of Mbanza Kongo, from independence in 1975 until the current project to make the city a UNESCO World Heritage Site. In the post-independence period, the narrative on the city of Mbanza Kongo and the Kingdom of the Kongo, at first, sought to counteract the colonial narrative and disqualify other traditional kongo narratives about the importance of the tradition, classifying them as outdated and allied with colonialism. In the mid-1980s, to this day, there was a radical change in the government’s narrative about the city of Mbanza Kongo, which became valued by the contact with Europeans, and with them the incorporation of education, catholicism and of buildings and so on. It is this narrative, which rescue the colonial narrative, the one sustained in the current project of making the city a UNESCO world heritage site.